Os efeitos do Programa Minha Casa Minha Vida para a população de baixa renda em Marília-SP: a construção de uma ilusão - Dumont, Tiago Vieira Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The central idea of this thesis is on understanding how the construction and production of housing comprises a trama urbana in Brazil. Through a sociological perspective and the historic rescue, we seek to highlight the effects and limitations of recent urban policy brazilian and, more specifically, the housing policy for the low-income population, focused on Program My Home My Life. It is understood that this Program aimed at democratizing the access to housing for people excluded from the housing market, resulting in a right to the city. Our hypothesis is tha the current housing policy is articulated with employment policy, it is necessary to so disjointed urban policy and in particular the urban policy and municipal Plans of Directors, causing damage to the population and the city. Is taking the city of Marília as a universe of social research, more specifically, the problematization of the housing issue, on the basis of the Program My House, My Life, that we are to demonstrate the importance that the housing is in the country. From the problem presented nicer note the gaps in the production of a housing policy that establish the practice of install, self-financing and benefited areas, the solutions that people can repair the deficit of housing policy and urban in the country, we still, the adoption or not of clientelistic practices in different governments. This process is analyzed over a historic route, which in situating the economic bias intrinsic to the production housing stock, as well as, to demonstrate how the promise of advances numeric live in households with another person with setbacks, as part of the population served by the program have been confined to areas that grow in a random manner, deficient and unattended, so the margin of municipal rights and collective benefits. With this research will try to understand, through a case study, in the municipality of stockholm, the social consequences and urban planning, such...

A idéia central desta dissertação esta na compreensão de como a construção e produção da habitação compõe a trama urbana no Brasil. Através de uma perspectiva sociológica e do resgate histórico, buscamos evidenciar os efeitos e as limitações da recente política urbana brasileira e, mais especificamente, a política habitacional para a população de baixa renda, focada no Programa Minha Casa Minha Vida. Entende-se que esse Programa objetiva democratizar o acesso à moradia para as populações excluídas do mercado imobiliário, resultando num direito a cidade. Nossa hipótese é de que a atual política habitacional, por está articulada à política de emprego, se impõe de modo desarticulada da política urbana e em especial da política urbana municipal e dos Planos Diretores, acarretando prejuízos à população e à cidade. É tomando a cidade de Marília como um universo de investigação social, mais especificamente, a problematização da questão da habitação, com base no Programa Minha Casa, Minha Vida, que pretendemos demonstrar a importância que a habitação assume no país. A partir da problemática apresentada buscamos observar as lacunas na produção de uma política habitacional que estabelecem na prática da autoconstrução, autofinanciamento e favelização, as soluções para que população possa reparar o déficit de políticas habitacionais e urbanas no país, verificamos ainda, a adoção ou não de práticas clientelistas em diferentes governos. Esse processo é analisado ao longo de um percurso histórico, o que nos permite situar o viés econômico intrínseco à produção habitacional, assim como, de demonstrar como a promessa de avanços numéricos coabita com retrocessos, já que parte da população atendida pelo programa tem sido confinada em áreas que crescem de forma aleatória, deficiente e desassistida, portanto à margem dos direitos urbanos e dos benefícios coletivos. Com esta ...
Keywords: Politica habitacional; Politica urbana; Habitação popular; Politicas publicas; Exclusão social; Public policy